Ein Gemenge von Emotionen als immanenter Bestandteil der Ausspracheschulung – Zu den störenden und fördernden Einflüssen der Emotionen auf den Ausspracheerwerbsprozess in der universitären Bildung im DaF-Bereich - Małgorzata Żytyńska (Linguistische Treffen in Wrocław, 2020)
This article presents the influence of emotions on the teaching and learning process, with particular emphasis on pronunciation classes at university level. The first chapters describe the terminological intricacies within emotions, feelings, moods etc., and then the positive and negative influence of emotions on the didactic process. The next part presents attempts to use emotions that support the learning process and to cool down difficult emotions that disorganise work in classes and negatively influence the learning process. A special case is phonetic education, which arouses many more emotions than in other classes. At the end, there is a reasonable proposal of exercises called etudes, which positively influence unwanted emotions and support emotions beneficial for the didactic process.